Result of study on developing forest seed region in Mongolia - S, Jamyansuren; B, Udval; N, Batkhuu; J, Bat-Erdene; Fischer, Michael (Proceedings of the Mongolian Academy of Sciences, 2018)
In other countries, they usually use auto road and railroad as borders of the forest seed regions. In case of Mongolia, this method is not suitable since sparse population, large distribution area of forests and large territory. Therefore, we used topographical features to determine borders of the seed regions. Satellite images in combination with DEM make it possible to define rivers, streams and mountain ridges as border of forest seed regions. Species included in forest seed regions are: Siberian larch (Larix sibirica Ldb.), Dahurian larch (Larix dahurica Turcz), Chekanovskii larch (Larix chekanowski Szaf.), Scotch pine (Pinus sylvestris L.), Siberian pine (Pinus sibirica Du Tour.), Siberian spruce (Picea obovate Ldb.), and Siberian fir (Abies sibirica Ldb.). Mongolian forests are mountain forests with high altitudinal variation and have dry growth condition hence, seed quality of the main tree species is declining recently. It is required to use seeds from the same seed region. Only if this is not possible the seeds should be obtained from regions with comparable ecological conditions. Local seed is the ones collected from the forests within the border of same seed region, and seed from the other regions are the ones collected from the other seed region. Seeds collected from the plain forests can be used for almost all forest regions, however seeds collected from mountainous regions can only be used within 200-400 m limit of the original altitude. We identified 19 seed regions for Siberian larch and 12 regions for Scots pine, 9 regions for Siberian pine, 6 regions for Siberian fir and 9 seed regions for Siberian spruce forests, respectively. Due to lack of genetic-selection study in Mongolia, this proposed forest seed regions can be considered as preliminary effort and it is possible to changed and improved based on more detailed research results. These forest seed regions proposed by project team can be used as fundamental material for establishing permanent forest seed supply based on genetic-selection characteristics of the forests in different regions in Mongolia.